Anti-inflammatory effects of para-quinone methide derivatives on ulcerative colitis - Qiu, Yue; Li, Xin; Zhang, Xu; Wang, Xiaotong; Wang, Xuekun; Yang, Jie; Liu, Guoyun (Frontiers in Pharmacology, 2024)
A series of para-quinone methide derivatives were evaluated their anti-inflammatory activity. Through the screening of the lipopolysaccharide (LPS)-induced inflammatory cell model in Raw264.7 cells, it was found that the inhibitory activity of meta-substituted derivatives on NO production was superior to that of ortho- and para-substituted derivatives. Among them, in the inflammatory cell model, the meta-trifluoromethyl substituted para-quinone methide derivative 1i had the best activity in inhibiting LPS-induced excess generation of NO. And 1i could effectively inhibit the increase of ROS in inflammatory cells, the expression of iNOS related to the production of NO, and the expressions of inflammation related initiating protein TLR4, pro-inflammatory cytokines IL-6 and TNF-, inflammasome NLRP3 and Caspase1. In the dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) mouse model, the active derivative 1i could inhibit DSS-induced colon shortening, and reverse DSS-induced pathological changes in colon tissue, such as inflammatory infiltration, structural destruction and crypt disappearance. 1i could effectively inhibit oxidative stress, inflammation and apoptosis in UC mice. Moreover, through the determination of serum biochemical indicators, tissue pathologies and tissue organ indexes, 1i could effectively reverse the damage to mouse liver and kidney caused by DSS, playing a protective role in liver and kidney of mice. In summary, 1i was an effective anti-inflammatory reagent and could be developed as a potential drug for anti-UC.